Small Bowel Intussusception Due to Rare Cardiac Intimal Sarcoma Metastasis: A Case Report - Chiarelli, Marco; Zago, Mauro; Tagliabue, Fulvio; Burati, Morena; Riva, Cristina; Vanzati, Alice; Dainese, Emanuele; Gabrielli, Francesco; Guttadauro, Angelo; De Simone, Matilde; Cioffi, Ugo (Frontiers in Surgery, 2021)
BACKGROUND Intimal sarcomas are rare malignant mesenchymal tumors arising from the heart and large blood vessels. Their intraluminal growth leads to vascular obstructive symptoms and peripheral neoplastic embolization. Direct infiltration of the lungs or metastases to the pulmonary system, occur in 40% of cases and extrathoracic spread is frequent, also in presentation. Intussusception is an unusual event in adults, accounting for less than 5% of bowel obstructions. In most cases it is caused by a malignancy and requires surgical resection. CASE PRESENTATION We describe a rare case of a 50-year-old man suffering of bowel obstruction due to intussusception sustained by a small bowel metastasis of a primary cardiac intimal sarcoma. One year and a half before the onset of abdominal symptoms, a grade II intimal sarcoma was removed from his left atrium and consequently he followed a chemotherapy protocol. Four months later a CT scan revealed local recurrence. Eighteen months after heart surgery he referred to the ER with abdominal pain. CT scan showed an ileal intussusception and the patient was scheduled for surgery. A tract of ten cm ileus was removed containing an intramural polypoid solid mass. Histological analyses revealed a grade II intimal sarcoma consistent with his first diagnosis. CONCLUSION Primary heart tumors are late found and often partially resected, therefore metastatic pathways are to be expected. Adult small bowel intussusception is a rare event and caused by a malignancy in one third of cases. Therefore, our recommendation is to always resect the tract involved in order to perform a proper diagnosis.